Erythema Multiforme Major in Angioimmunoblastic T-cell Lymphoma - Shoko Hattori; Fumi Miyagawa; Keiko Fukuda; Kohei Ogawa; Hideo Asada (Medical Journals Sweden, 2021)
Abstract is missing (Short communication)